2009
DOI: 10.1160/th08-08-0511
|View full text |Cite
|
Sign up to set email alerts
|

Levels of inflammatory markers and the development of the post-thrombotic syndrome

Abstract: SummaryThe post-thrombotic syndrome (PTS) occurs frequently after deep venous thrombosis (DVT) despite appropriate anticoagulant therapy. A close relationship between inflammation and thrombosis exists. While the inflammatory process at the time of DVT appears to improve thrombus resolution, it may promote destruction of venous valves, valvular reflux and subsequent development of PTS. We prospectively evaluated the association between levels of four cytokines (IL-6, IL-8, IL-10 and MCP-1), two adhesion molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 46 publications
3
60
0
2
Order By: Relevance
“…18,35 Sustained venous hypertension can cause structural and biochemical abnormalities of the vein wall, resulting in pathological effects in the skin and subcutaneous tissues such as edema, hyperpigmentation, varicose veins, and ulceration. 24 Several studies have reported associations between elevated levels of various inflammation markers and PTS development 35,36 (see Role of Biomarkers to Predict PTS).…”
Section: Clinical Manifestations and Pathophysiology Characteristic Smentioning
confidence: 99%
See 1 more Smart Citation
“…18,35 Sustained venous hypertension can cause structural and biochemical abnormalities of the vein wall, resulting in pathological effects in the skin and subcutaneous tissues such as edema, hyperpigmentation, varicose veins, and ulceration. 24 Several studies have reported associations between elevated levels of various inflammation markers and PTS development 35,36 (see Role of Biomarkers to Predict PTS).…”
Section: Clinical Manifestations and Pathophysiology Characteristic Smentioning
confidence: 99%
“…Shbaklo et al 36 reported that patients with PTS had significantly higher mean levels of interleukin-6 and intercellular adhesion molecule-1 than those without PTS. Roumen-Klappe et al 35 noted that higher levels of interleukin-6 and C-reactive protein were associated with greater venous outflow resistance 3 months after DVT, but their association with clinical PTS was weak or absent.…”
Section: Role Of Biomarkers To Predict Ptsmentioning
confidence: 99%
“…The inflammatory response elicited after a thrombotic event is needed for resolution of the thrombus. 29 We speculate that this physiological response may contribute to disruption of the blood-retina barrier and formation of oedema due to the action on tight junctions mentioned earlier.…”
Section: Il-8 and Mcp-1 In Brvo Macular Oedemamentioning
confidence: 63%
“…With regard to biomarkers that could help to predict PTS, recent studies have reported that elevated levels of markers of inflammation (eg, ICAM-1, interleukin-6, and C-reactive protein) 49,50 and D-dimer 40,51 early after diagnosis or within a few months of DVT were associated with the development of PTS. A large, prospective multicenter study that is examining the predictive role of various markers of inflammation, D-dimer, and thrombophilia in the development of PTS is currently under way.…”
Section: Individual Risk Factors For Ptsmentioning
confidence: 99%